Main Issues of Value-Added Tax Dispute in Indonesia: A Note from 2019 Tax Court Decrees - Saptono, Prianto Budi; Khozen, Ismail; Ayudia, Cyntia (Universitas Swadaya Gunung Jati, 2021)
AbstractDue to the lengthy, complicated, and expensive process, tax disputes in Indonesia are often in the spotlight. Moreover, the frequently recurring disputes for similar cases add to the long list of the issues. To that end, this study has two objectives. The first is to analyze Value Added Tax (VAT) concepts in Indonesia's regulations. The second is to analyze the VAT dispute according to the sample generated from the 2019 Tax Court decree. Thus, it is qualitative research with inductive reasoning using data collection techniques through documentation and literature studies. This study elucidates concepts underlying VAT regulations that have received scant attention in the prior literature. The core of the VAT dispute issues stems from divergent perspectives on VAT provisions between the tax authority and taxable persons. The primary issues in VAT disputes generally involve disagreements over interpretation and inaccuracies in supporting evidence on both the input and output sides. Given that the 2019 Tax Court decree upholds only 32% of the tax authorities' corrections, knowledge of the VAT concept is critical for readers of laws and regulations to grasp the underlying concept of the regulation.Keywords: Tax dispute; Value-added tax; Tax court decision. Abstrak Sengketa pajak di Indonesia sering menjadi sorotan karena prosesnya yang panjang, rumit, dan memakan biaya. Selain itu, sengketa yang kerap kali berulang untuk kasus serupa menambah daftar panjang masalah. Untuk itu, kajian ini bertujuan untuk menganalisis penerapan konsep PPN di dalam ketentuan perundang-undangan perpajakan Indonesia. Kajian ini juga ditujukan untuk mensintesiskan sengketa PPN dengan sampel dari putusan Pengadilan Pajak tahun 2019. Studi ini menggunakan pendekatan kualitatif dengan penalaran induktif yang menggunakan teknik pengumpulan data berupa studi dokumentasi dan literatur. Kajian ini mengungkap konsep-konsep di balik peraturan PPN yang belum banyak dibahas literatur sebelumnya ketika inti permasalahan sengketa PPN justru berpangkal pada perbedaan sudut pandang atas ketentuan PPN tersebut di antara otoritas pajak dan pengusaha kena pajak (PKP). Isu utama dalam sengketa PPN secara umum meliputi perbedaan penafsiran dan ketidakakuratan bukti pendukung, baik di sisi input maupun output. Mengingat putusan Pengadilan Pajak 2019 hanya mempertahankan 32% koreksi otoritas pajak, tampak bahwa pengetahuan tentang konsep PPN sangat penting di dalam memberikan pemahaman akan konsep yang mendasari peraturan tersebut.Katakunci: Sengketa pajak; Pajak pertambahan nilai; Putusan pengadilan pajak.